Catalogo de los Miridae (Heteroptera) de Nicaragua - Maes, J.-M.=700 1 Carvalho, J.C.M.
(Es, Es)
Ilus., 309 ref.
Keywords: CLASIFICACION; MIRIDAE; HETEROPTERA; HUESPEDES; ENEMIGOS NATURALES; DISTRIBUCION GEOGRAFICA; NICARAGUA; REVISTA NICARAGUENSE DE ENTOMOLOGIA